Pendataan Pengunjung Melalui Counter Entrance Berbasis Fingerprint di Perpustakaan - Gusriani, Moliza; Jayanti, Lida Dara; Fatwanto, Agung (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
There are various innovations that can be carried out by libraries, one of which is by designing technology systems to make things easier for librarians and users. The purpose of this article is to discuss innovation by implementing a Fingerprint system connected to an automatic Flap Barrier. This research method is a system design method using the Software Development Life Cycle Waterfall model which is supported by literature studies as relevant sources through journals, books and previous research. The results obtained are that there is an innovative design development that the library can implement, namely the Fingerprint system, where users are connected to the Automatic Flap Barrier. This can make it easier for librarians to know the identity of library membership without carrying a KTM (Student Identification Card). This Fingerprint system design can be applied to University libraries which are specifically designed to make it easier for librarians and users. This research is a new innovation in library membership services with the aim of minimizing space and time and this design is recommended to be implemented according to its intended purpose.